2023
DOI: 10.1002/mnfr.202300076
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Supplementation Assists Sorafenib in Slowing Skeletal Muscle Atrophy in H22 Tumor‐Bearing Mice via Reversing Abnormal Glucose Metabolism

Abstract: ScopeCachexia, which is often marked by skeletal muscular atrophy, is one of the leading causes of death in cancer patients. Astaxanthin, a carotenoid obtained from marine organisms that can aid in the prevention and treatment of a variety of disorders. In this study, to assess whether astaxanthin ameliorates weight loss and skeletal muscle atrophy in sorafenib‐treated hepatocellular carcinoma mice is aimed.Methods and resultsH22 mice are treated with 30 mg kg−1 day−1 of sorafenib and 60 mg kg−1 day−1 of astax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…10 In addition, astaxanthin slowed down skeletal muscle atrophy and weight loss in tumor-bearing mice during sorafenib treatment. 11 It is noteworthy that we also detected significant changes in the composition of the gut microbiota in mice who received astaxanthin supplementation. 10 Numerous studies in recent years have revealed that gut microbiota plays a key role in cancer-associated skeletal muscle atrophy.…”
Section: Introductionmentioning
confidence: 62%
“…10 In addition, astaxanthin slowed down skeletal muscle atrophy and weight loss in tumor-bearing mice during sorafenib treatment. 11 It is noteworthy that we also detected significant changes in the composition of the gut microbiota in mice who received astaxanthin supplementation. 10 Numerous studies in recent years have revealed that gut microbiota plays a key role in cancer-associated skeletal muscle atrophy.…”
Section: Introductionmentioning
confidence: 62%
“…The findings of our previous study have provided confirmation that the inclusion of astaxanthin as a dietary supplement during sorafenib treatment yields significant efficacy in the inhibition of tumor progression. 19 The observed phenomenon is likely to be associated with the augmented antitumor immune response elicited by astaxanthin. Indeed, there have been reports indicating that astaxanthin plays a role in inhibiting the cell cycle of tumor cells and promoting apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were inoculated with H22 tumor cells subcutaneously in the right axilla after one week of adaptive rearing to construct the H22 tumor-bearing mice, as detailed in our previous report. 19 When the mice subcutaneous tumor models grew to about 100 mm 3 , the mice were randomly divided into four groups ( n = 8). The experimental groups were: (1) model group (M group, n = 8), which was given 0.5% sodium carboxymethyl cellulose administered by gavage daily; (2) sorafenib group (S group, n = 8), which was given 30 mg kg −1 of sorafenib administered by gavage daily; (3) astaxanthin group (A group, n = 8), which was given 60 mg kg −1 of astaxanthin administered by gavage daily; (4) sorafenib combined with Astaxanthin group (SA group, n = 8), which was given 30 mg kg −1 of sorafenib treatment and 60 mg kg −1 of astaxanthin administered by gavage daily.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations